Probabilistic Evaluation of Grouting Reinforcement on Settlement Control Effectiveness in Shield Tunneling Construction - LAN Mulin; SHEN Mengfen; HE Su; XU Quan; CHEN Zhehui; BAO Lichun (Chengshi guidao jiaotong yanjiu, 2024)
［Objective］In order to reduce the ground disturbance when the shield tunnel underpasses buildings, it is necessary to study the settlement control effect of grouting reinforcement during shield tunneling under the buildings. ［Method］Taking the shield tunnel of Hangzhou Metro Line 12 passing under the pile foundation building in a certain section of Xiasha Road as an example, and based on the FLAC 3D finite difference software, two methods of deterministic analysis and reliability analysis are adopted respectively to evaluate the effectiveness of grouting reinforcement measures in controlling foundation settlement caused by shield construction. ［Result & Conclusion］In the deterministic analysis, both the on-site measured data and the numerical analysis results show that the maximum building foundation settlement occurs on one side of the tunnel that is first excavated; grouting reinforcement technology can effectively reduce the building foundation settlement caused by shield excavation, making the building settlement value meets the specification design requirements. In the reliability analysis, the cohesion and internal friction angle are used as random variables, and the Latin hypercube sampling-response surface-finite difference method is adopted to evaluate the control effect of grouting reinforcement. It is found that the grouting reinforcement can effectively improve the structural reliability of the building foundation and significantly reduce the uncertainty of the calculated settlement value. Compared with the deterministic analysis method, the reliability analysis method is more reasonable in describing building foundation structure safety by taking the uncertainty of the parameters into account, and can be used to evaluate the effectiveness of control measures in complex shield tunnel excavation projects.